Three Dimensional CFD Studies of a Solar Chimney: Effect of Geometrical Parameters and Diurnal Variations on Power Generated - Ganguli, Arijit A.; Deshpande, Sagar (Frontiers in Chemical Engineering, 2020)
Solar power has gained particular importance in the current era due to a need of harnessing the biggest and cleanest source of energy, i. e., solar energy. One of the most innovative as well as simple technique to generate solar power is using a solar chimney. Solar chimney power plant, however, requires high investment costs and traditionally have been of very low efficiency. Mathematical and CFD models pose a good way to optimize performance of such kind of chimneys. Several factors affect the power generation from a solar chimney including geometric factors (like collector diameter, chimney height) and diurnal temperature variations. The challenge however lies in diurnal variation of temperatures and hence unstable power generation. In the present work, a pilot scale CFD model of solar chimney (of prototype of Manzanares Chimney, Spain, Haaf, 1984) was built and validated with experimental data and analytical models from the literature ( <10% deviation from experimental data). Subsequently, flow patterns were studied and a parametric study was carried out for the chimney for the key parameters, namely, chimney height, and collector diameter. For the first time effect of diurnal variations on the power generated was studied. With consideration of diurnal variations, power generation during night was found to be a linear function of chimney height and collector diameter; while, during day time, the power-generated increased exponentially with variation in collector diameter and chimney height.